Optimalisasi Pengisian Jabatan Pimpinan Tinggi Berbasis Merit di Lingkungan Pemerintah Provinsi Riau - Prabowo, Harry (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The implementation of the merit system in the management of Riau Province's ASN still faces challenges which are characterized by the fact that performance in aspects of promotion and transfer is low. This is because the current JPT filling does not yet implement a talent management mechanism as mandated in the merit system index assessment. This issue is important to address because it will have an impact on the quality of bureaucratic leadership and overall government performance. This policy paper uses a literature study approach and SWOT analysis to compare two alternative JPT filling policies, namely open selection and talent management. The results of the analysis show that talent management has strategic advantages to be implemented, with dominant internal strengths and external opportunities compared to the open selection mechanism currently used. Thus, it is recommended that the Governor of Riau formulate a policy in the form of a governor's regulation as a basis, guideline and technical instructions for implementing talent management. Furthermore, the Riau Province Regional Civil Service Agency as the regional apparatus that carries out personnel affairs can implement this policy gradually and comprehensively. The implementation of this policy is expected to improve the quality of bureaucratic leadership, encourage accelerated improvement in the quality of public services and achieve regional development goals in Riau Province, as well as contribute to increasing the merit system index assessment score.